2022
DOI: 10.5114/ait.2022.113488
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-invasive ventilation on intra-abdominal pressure

Abstract: Intra-abdominal hypertension (IAH) is defined as a repeated or sustained intra-abdominal pressure (IAP) above or equal to 12 mm Hg, and abdominal compartment syndrome (ACS) is defined as a sustained IAP above 20 mm Hg associated with new organ dysfunction or failure [1].A previous case report described how noninvasive ventilation (NIV) caused aerophagia, gastric distension and increased IAP, culminating in ACS and cardio-respiratory arrest. Resuscitative efforts included gastric decompression with a nasogastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Previously, case reports have described IAH and ACS developing in patients requiring NIV. In a clinical study in 35 patients receiving NIV, the use of NIV was not associated with an increase in IAP after 24 h of NIV, also in patients requiring pressure support above 10 cmH 2 O [32]. On the basis of this finding, IAH should not be considered a contraindication to start NIV when considered necessary.…”
Section: Conditions Commonly Associated With Intra-abdominal Hyperten...mentioning
confidence: 81%
“…Previously, case reports have described IAH and ACS developing in patients requiring NIV. In a clinical study in 35 patients receiving NIV, the use of NIV was not associated with an increase in IAP after 24 h of NIV, also in patients requiring pressure support above 10 cmH 2 O [32]. On the basis of this finding, IAH should not be considered a contraindication to start NIV when considered necessary.…”
Section: Conditions Commonly Associated With Intra-abdominal Hyperten...mentioning
confidence: 81%
“…Numerous pathologies associated with gastric distension have been identified and reported to be associated with NIPPV, but to our knowledge, this is the first case in which NIPPV resulted in significant distension of an existing hiatal hernia to the point of mediastinal tamponade. Although Adrian Regli's research demonstrated that non-invasive ventilation was not correlated with an increase in intra-abdominal pressure during a 72-hour period [3], cases of postoperative air leakage during NIPPV support have been made. Jean-Lavaleur M et al described a case of gastric perforation with NIPPV; the patient had a full recovery after primary closure [4].…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to attempt validation of IAP rect measurements against the gold standard IAP ves in an ICU-setting [9]. The inclusion of sedated patients, in whom confounding variables are lower, and the strict protocol are strengths of this study [26]. However, the small sample size, the poor description of patient demographics, high drop-out rate and the incompletely performed protocol due to patient or technique related issues are weaknesses and may have underpowered our study results.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%